Välfärdsindikatorer vid slakt av nöt och gris - Wikars, Linnea (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
Animal welfare is a growing concern in our society. The well-being of our livestock production has not only ethical concerns from the consumers, but it also affects the meat quality. Assessing animal welfare at the abattoir could be challenging, as stressful situations are common. Carcass damages lead to financial losses to both the abattoir and animal producers, as a result of carcass downgrading and rejections. The intention of this study was to investigate which welfare indicators can be used during slaughter of cattle and pigs, and whether good animal welfare is economically beneficial. Information have been obtained through scientific articles and reports, but also on the websites of The Swedish Board of Agriculture and The National Food Agency. Stressful situations during slaughter could be transport, regrouping, handling, and lairage. Welfare indicators are limited in numbers during slaughter. Indicators mentioned in this study are lameness, bruises and injuries, pH, meat defects (DFD and PSE) and quality. Meat defects, such as DFD or PSE, are dependent on pH which descends, while a descending pH is dependent on the pre-slaughter stress levels of the animal. Post slaughter, the carcasses are being classified by their usefulness. This assessment helps the animal producers to produce high quality products while at the same time meeting the market's requirements. Welfare during slaughter is important, both on the basis of the animals' intrinsic value, but also on the quality of the meat product. There are limited welfare indicators associated with slaughter; including lameness, bruising, body injury, pH of the meat and quality (including DFD and PSE). Although lameness does not affect meat quality to the same extent as the other indicators, it has an impact on animal welfare. Improving animal welfare, where animals’ have less prevalence of bruises and injuries and are less stressed before and during slaughter, leads to higher quality of carcass and meat and thus higher prices on the product. These welfare indicators can be set in relation to economic benefits and affect the working methods and situations of abattoirs and producers in the future.